Tradução, adaptação cultural e validade de conteúdo do programa de treinamento espanhol “empecemos” para pais - Chohfi, Maria Cecilia Fricke Siqueira (2020)
Recently lots of changes occurred when it comes to family models: the number of caregivers, the school model, the children's daily activities and the excessive amount of stimuli. These factors caused researchers to acknowledge such phenomena and to think about the importance of parental psychologic interventions as an instrument to prevent or improve behavioral problems in early childhood. Studies have shown that there are many benefits resulting from good parental practices; but programs in Brazil lack structure and methodological clarity, making it difficult to analyze their results and to use them. For that matter, a training that is very effective regarding interventions is called Empecemos, a Spanish program of parental intervention designed in 12 sessions to be deployed in a group of parents or caregivers of children between ages 5 to 11. Empecemos aims to potentialize positive interactions with children through positive reinforcement and shared activities. The goal of the present study was to translate, to adapt culturally and to validate the content inside of the program's manual so it may be suitable to use in Brazil. To do so, this work was divided into five phases: 1) authorization from the original author; 2) translation of the manual to Brazilian Portuguese by a professional that is native to Spanish language and fluent in Portuguese, and by another native in Brazilian Portuguese and fluent in Spanish; 3) cultural adaption of diverging words and expressions between the two translations; 4) synthesis of the two translated manuals and 6) validity of content, executed by five psychologists who are experts in parental interventions to attest if the content semantically equals the original text. Results show an average of 83,3% of positive margin for all sessions translation and adaptation and 95,8% off approval regarding the program’s format. This indicates that the program’s version in Brazilian Portuguese equals semantically and objectively to the original Spanish text and that it presents itself as a better structured alternative for deployment in Brazil.